Reforming Education from the Inside-Out: A Study of Community Engagement and Educational Reform in Rural Alaska - James W. Kushman; Ray Barnhardt (Journal of Research in Rural Education, 2001)
This paper presents a study ofseven rural Alaska communities engaged in reforms designed to increase community engagement and parent involvement in education, leading ultimately to lasting school-community partnerships that benefit all students. The primary reform effort was called Alaska Onward to Excellence (AOTE), which took place in small rural communities spanning western, central, and southeast Alaska. A cross-case analysis, conducted by research teams including researchers, school practitioners, and community members, resulted in four key findings. First, reform efforts in small communities require an inside-out approach in which educators must first develop trusting relationships with community members, and then work with the community to design educational programs around the local place, language, and culture. Second, parents and teachers need to expand their conceptions ofparent roles beyond the notion of parents supporting the school to include roles in which parents are active participants in school life and decisions. Third, school and district leaders must move from top-down to shared leadership so that the ownership for school reform is embedded in the community rather than with school personnel who constantly come and go. Finally, educators and educational reformers must recognize that education in rural Alaska has a larger purpose than teaching academic skills and knowledge.